The Influence Of Product Quality, Price, And Celebrity Endorsement On Purchase Decisions Through Brand Image As An Intervening Variable For Realme Smartphones: Pengaruh Kualitas Produk, Harga Dan Celebrity Endorsement Terhadap Keputusan Pembelian Melalui Citra Merek Sebagai Variabel Intervening Smartphone Realme - Wahyuningtyas, Citra Riyana; Violinda, Qristin; Prabowo, Heri (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of conducting the current research is to test and analyze the influence of product quality, price and celebrity endorsement on purchasing decisions through brand image as an intervening. The data collection method used in this study uses a survey by distributing it to respondents who have met the criteria. Then it was processed using Smart PLS version 3 with a total of 385 respondents. The latest in this study has the addition of variables that are different from previous research and different research locations or places so that the results found will be different. The results of this study show that product quality and influence purchase decisions. In addition, celebrity endorsement does not affect the purchase decision, it can be concluded that the purchase decision is not influenced by celebrity endorsement but is influenced by other factors that affect the purchase decision. Meanwhile, brand image, which is a mediating variable, is able to mediate between the quality of the product, the price and celebrity endorsement to the purchase decision.